In Gods we trust: the evolutionary landscape of religion - Atran, Scott (Evolution and cognition, 2004)
This ambitious, interdisciplinary book seeks to explain the origins of religion using our knowledge of the evolution of cognition. A cognitive anthropologist and psychologist, Scott Atran argues that religion is a by-product of human evolution just as the cognitive intervention, cultural selection, and historical survival of religion is an accommodation of certain existential and moral elements that have evolved in the human condition.